CORRELATION BETWEEN WORK DURATION AND DRIVER SITTING POSITION WITH LOW BACK PAIN OF THE DRIVERS AT MALENGKERI STATION MAKASSAR - Haristiani, Ruris; Marten, Ruth (Universitas Islam Negeri Alauddin Makassar, 2020)
Low back pain or commonly known as lower back pain is a complaint of pain,stiffness, or muscle tension in the lumbar region below of the ribs to the bottom crease of the buttocks. It is usually accompained by the spread of pain to the limb area. One of the causes is the duration of work and the wrong sitting position. The purpose of this study is to determine the correlation between work duration and driver sitting position with low back pain of the drivers at Malengkeri Station Makassar. The type of research is quantitative with cross-sectional research design. This research was conducted at Station Tamalate Malengkeri Makassar in July 2018. The number of sample is 81 respondents by total sampling technique. The results of the analysis uvivariat showed that the number of respondents with low back pain complaint is 58 respondents (71.6%) and without complaint is 23 respondents (28.4%). Ideal work duration is 22 respondents (27.25) and not ideal is 59 respondents (72.8%). Good sitting position is 27 respondents (33.3%) and that are bad sitting position is 54 respondents (66.7%). The statistical test using is Chi-square analysis with a significance level of 0,005. The result showed there is a signficant correlation between work duration with low back pain (p=0.000 < 0,05) and significant correlation between driver sitting position with low back pain (p=0.000 < 0,05). It can be concluded that there is correlation between work duration and driving sitting position with low back pain of the drivers at Malengkeri Station Makassar. Keywords: Low back pain, duration of work, sitting position.